2007
DOI: 10.1088/0029-5515/47/10/s16
|View full text |Cite
|
Sign up to set email alerts
|

Overview of TJ-II experiments

Abstract: This paper presents an overview of experimental results and progress made in investigating the link between magnetic topology, electric fields and transport in the TJ-II stellarator. The smooth change from positive to negative electric field observed in the core region as the density is raised is correlated with global and local transport data. A statistical description of transport is emerging as a new way to describe the coupling between profiles, plasma flows and turbulence. TJ-II experiments show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Note that the minimum value of the weak reversed shear safety factor q is slightly below 1. It can be observed that the q-profile is flat in the plasma core with q 0 ≈ 1; such a core-flat q-profile with integer q rational surface has been confirmed to be favorable for ITB triggering and maintenance by a series of experimental reports, such as on ASDEX Upgrade [47], JET [9,10,22], JT-60U [48] and DIII-D [49] devices, and even on a stellarator [50]. The main parameters are as follows: inverse aspect ratio ε = a/R = 0.237, triangularity δ = 0.43, elongation κ = 1.6, on-axis magnetic field B 0 = 1.58 T, electron central density In (e), the blue curve and blue dotted line represent the safety factor q = 1 and its corresponding radial location, respectively, and the shaded area indicates the ITB region.…”
Section: Experimental Observation and Simulation Setupmentioning
confidence: 73%
“…Note that the minimum value of the weak reversed shear safety factor q is slightly below 1. It can be observed that the q-profile is flat in the plasma core with q 0 ≈ 1; such a core-flat q-profile with integer q rational surface has been confirmed to be favorable for ITB triggering and maintenance by a series of experimental reports, such as on ASDEX Upgrade [47], JET [9,10,22], JT-60U [48] and DIII-D [49] devices, and even on a stellarator [50]. The main parameters are as follows: inverse aspect ratio ε = a/R = 0.237, triangularity δ = 0.43, elongation κ = 1.6, on-axis magnetic field B 0 = 1.58 T, electron central density In (e), the blue curve and blue dotted line represent the safety factor q = 1 and its corresponding radial location, respectively, and the shaded area indicates the ITB region.…”
Section: Experimental Observation and Simulation Setupmentioning
confidence: 73%
“…Rotation velocities in the TJ-II stellarator have been associated with E × B plasma rotation with maxima around 4 km s −1 in typical ECH plasmas [24,25]. Using the times at which the (vacuum) 8/5 and 5/3 resonances occupy the region ρ ≈ 0.7, and based on discharges with similar density ( n ≈ 0.7 × 10 19 m −3 ) at those times, we find frequencies around 40 kHz (8/5) and 27 kHz (5/3).…”
Section: Description Of the Dischargesmentioning
confidence: 99%
“…In the TJ-II stellarator [9], previous studies of impurity confinement using LBO have focused on heavy (iron) impurities [10][11][12] where moderate core confinement times (τ r ∼ 10 ms) were observed for low plasma densities, n e 0.6 × 10 19 m −3 , when the core radial electric field, E r , is positive. However, in the vicinity of the density value where a transition to negative E r occurs a significant rise in impurity confinement time, τ r , to ∼20 ms was observed, this being most appreciable with neutral beam injection (NBI) heating [12].…”
Section: Introductionmentioning
confidence: 99%